KARAKTERISTIK TULISAN NARASI FIKSI BERBAHASA ARAB MAHASISWA PENUTUR ASLI BAHASA INDONESIA - Nurhidayati Nurhidayati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This study is carried out to answer the research questions what are the characteristics of intrinsic elements, include is plot, character, and background   of the Arabic fictitious narrative writing of Indonesian language native students? This study is qualitative. The approach used is socio-psycho structural. Data are verbal such as: (1) fictitious narrative writing, (2) interview transcript, and (3) fieldnotes. Data of fictitious narrative writing were taken from of the students’ portfolio writing narative  fiction  of  final  tasks  semester  of  writing  lucture  1.  Data  of  interview transcript  and  fieldnotes  of  the  teaching  process  are  data  used  to  clarify  and complete   the  data  of  fictitious   narrative   writing.   Data  were  analyzed   using interactive  analysis.  Based on the findings  be concluded  that first,   plot linier is domination plot in the writing fiction, Neaming character and fisiologis description is domination character was described as direct and non-direct description, and story background is domination background with used to descriptive of location and time of story without psichologis meaning.